Safety, Tolerability, and Immunogenicity of Interferons - Michael G. Tovey; Christophe Lallemand (MDPI AG, 2010)
Interferons (IFNs) are class II cytokines that are key components of the innate immune response to virus infection. Three IFN sub-families, type I, II, and III IFNs have been identified in man, Recombinant analogues of type I IFNs, in particular IFNα2 and IFNβ1, have found wide application for the treatment of chronic viral hepatitis and remitting relapsing multiple sclerosis respectively. Type II IFN, or IFN gamma, is used principally for the treatment of chronic granulomatous disease, while the recently discovered type III IFNs, also known as IFN lambda or IL-28/29, are currently being evaluated for the treatment of chronic viral hepatitis. IFNs are in general well tolerated and the most common adverse events observed with IFNα or IFNβ therapy are "flu-like" symptoms such as fever, headache, chills, and myalgia. Prolonged treatment is associated with more serious adverse events including leucopenia, thrombocytopenia, increased hepatic transaminases, and neuropsychiatric effects. Type I IFNs bind to high-affinity cell surface receptors, composed of two transmembrane polypeptides IFNAR1 and IFNAR2, resulting in activation of the Janus kinases Jak1 and Tyk2, phosphorylation and activation of the latent cytoplasmic signal transducers and activators of transcription (STAT1) and STAT2, formation of a transcription complex together with IRF9, and activation of a specific set of genes that encode the effector molecules responsible for mediating the biological activities of type I IFNs. Systemic administration of type I IFN results in activation of IFN receptors present on essentially all types of nucleated cells, including neurons and hematopoietic stem cells, in addition to target cells. This may well explain the wide spectrum of IFN associated toxicities. Recent reports suggest that certain polymorphisms in type I IFN signaling molecules are associated with IFN-induced neutropenia and thrombocytopenia in patients with chronic hepatitis C. IFNγ binds to a cell-surface receptor composed of two transmembrane polypeptides IFGR1 and IFGR2 resulting in activation of the Janus kinases Jak1 and Jak2, phosphorylation of STAT1, formation of STAT1 homodimers, and activation of a specific set of genes that encode the effector molecules responsible for mediating its biological activity. In common with type I IFNs, IFNγ receptors are ubiquitous and a number of the genes activated by IFNγ are also activated by type I IFNs that may well account for a spectrum of toxicities similar to that associated with type I IFNs including "flu-like" symptoms, neutropenia, thrombocytopenia, and increased hepatic transaminases. Although type III IFNs share the major components of the signal transduction pathway and activate a similar set of IFN-stimulated genes (ISGs) as type I IFNs, distribution of the IFNλ receptor is restricted to certain cell types suggesting that IFNλ therapy may be associated with a reduced spectrum of toxicities relative to type I or type II IFNs. Repeated administration of recombinant IFNs can cause in a break in immune tolerance to self-antigens in some patients resulting in the production of neutralizing antibodies (NABs) to the recombinant protein homologue. Appearance of NABs is associated with reduced pharmacokinetics, pharmacodynamics, and a reduced clinical response. The lack of cross-neutralization of IFNβ by anti-IFNα NABs and vice versa, undoubtedly accounts for the apparent lack of toxicity associated with the presence of anti-IFN NABs with the exception of relatively mild infusion/injection reactions.